Are Changes in Inflation Expectations Capitalized into Stock Prices? A Micro-Firm Test for the Nominal Contracting Hypothesis - Dokko, Yoon (The Review of Economics and Statistics, 1989)
Yoon Dokko, Are Changes in Inflation Expectations Capitalized into Stock Prices? A Micro-Firm Test for the Nominal Contracting Hypothesis, The Review of Economics and Statistics, Vol. 71, No. 2 (May, 1989), pp. 309-317